Budget management and aquaculture development in the Huanuco region, 2021 - Espiritu-Rueda, Deni M. (2023)
Objective. To analyze the effect of budget management on aquaculture development in the Huanuco region (Peru), 2021. Methods. The study had a quantitative approach, of explanatory level, based on applied research, with a non-experimental, cross-sectional and correlational-case study design. The population sample consisted of 129 fish farmers who cultivated rainbow trout in the region, who answered 2 questionnaires with previous validation. Spearman's rho correlation test was used for inferential analysis. Results. The results showed that 71% (92) of the fish farmers had a regular level of budget management and 11% (9) had a deficiency; with respect to aquaculture development, 45% (58) of the fish farmers had a regular level. Conclusions. There is a moderate positive correlation of r = 0.684 and a significance level of p = 0.000 between the study variables, so it can be deduced that budget management significantly influences the development of aquaculture in the Huánuco region, 2021.